2016
DOI: 10.21474/ijar01/2185
|View full text |Cite
|
Sign up to set email alerts
|

Agro Morphological Characterization and Study of Grain Yield of Algerian Durum Wheat (Triticum DURUM.DESF.

Abstract: Improvement and rehabilitation passes necessarily by a characterization step and a performance evaluation in view of future use. In this context, a collection of 26 accessions of durum wheat (Triticum durum.desf) was studied based on an assortment of agro morphological and physiological traits. This study took place during the campaign of 2011/2012 on the ITGC site of el khroub station. This site represents the highest Algerian eastern plains. The results showed highly significant varietal differences for all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
2
0
0
Order By: Relevance
“…In addition, the RWC shows negative correlations with the following parameters: AFL, LSP and LB this means that the narrow AFL and the characteristics of a short spike contribute to a limitation of water losses. Similar results have been reported by other studies (Salmi 2015;Khennaoui et al 2016). On the other hand, it appears that varieties with a high height have a high RWC; these results correspond to those obtained by Jatoi et al (2011).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, the RWC shows negative correlations with the following parameters: AFL, LSP and LB this means that the narrow AFL and the characteristics of a short spike contribute to a limitation of water losses. Similar results have been reported by other studies (Salmi 2015;Khennaoui et al 2016). On the other hand, it appears that varieties with a high height have a high RWC; these results correspond to those obtained by Jatoi et al (2011).…”
Section: Discussionsupporting
confidence: 93%
“…The varieties Wahbi, Waha, and Semito showing the highest RWCs, are relatively the least productive, with the exception of the variety Cirta, which seems to have little tolerance for the yield compared to other varieties. This is perfectly similar to the results obtained by Khennaoui et al (2016) who recorded a negative relationship (R = -0.466) between RWC and Yield, and on the basis of previous studies, they have been concluded that genotypes tolerant to abiotic stress are less productive and lose less water leaf area per unit of time. In addition, the RWC shows negative correlations with the following parameters: AFL, LSP and LB this means that the narrow AFL and the characteristics of a short spike contribute to a limitation of water losses.…”
Section: Discussionsupporting
confidence: 91%